Resolving electrochemical incompatibility between LATP and Li-metal using tri-layer composite solid electrolyte approaches for solid-state Li-metal batteries - Kibret, Desalegn Yilma; Mengesha, Tadesu Hailu; Walle, Kumlachew Zelalem; Wu, Yi–Shiuan; Chang, Jeng-Kuei; Rajan, Jose; Yang, Chun-Chen (Elsevier Ltd, 2024)
Due to its excellent air stability, low cost, and high ionic conductivity, Li1.3Al0.3Ti1.7(PO4)3 (LATP) has emerged as a viable option for solid-state lithium batteries (SSLBs). However, the irreversible reactivity between LATP and the Li-metal anode severely restrict its electrochemical performances. Herein, a tri-layer composite solid electrolyte (t-CSE1) comprised of LATP, PVDF-HFP, SN, and LiTFSI as the middle layer and Al-LLZO, PVDF-HFP, SN, and LiTFSI as the top and bottom layers is prepared to solve these prominent limitations since Al-LLZO is stable towards Li metal anode. As a result, the lithium plating-stripping lifetimes for the Li||Li symmetry cell is prolonged from 550 to 1950 h at 0.1 mA cm− 2 without any residual redox products. In addition, the as-prepared tCSE1 exhibited excellent ionic conductivity (ca. 6.46 × 10− 4 S cm− 1 at room temperature), high lithium-ion transference number (ca. 0.69) and remarkable mechanical strength (ca. 12.82 MPa). Furthermore, the Li|| LiFePO4 (Li||LFP) full cell achieved significantly improved long cycle performances of 500 cycles with 80.31 % capacity retention and 99.93 % average coulombic efficiency at 0.2C. Moreover, the Li||LFP full cell showed 85.53 % capacity retention and 99.95 % coulombic efficiency after 200 cycles at 0.5C at room temperature. Thus, this study gives an insight into how to prevent the electrochemical incompatibility between LATP and Li metal for SSLBs.